Pendidikan Masyarakat di Masa Pandemi COVID-19: Studi Kasus Peran Orang Tua dalam Pendidikan Anak - Suryadi Suryadi (UIN Siber Syekh Nurjati Cirebon, 2020)
Abstract Empowerment is an activity in which a person could handle problems or from hard situation thus he has the power to move forward, it could influence for his life in the environment. The empowerment that occurs in parents during a pandemic period actually appears as a respond to unexpected events. A condition and situation that must be done, either in the form of children's learning during the pandemic, as well as taking other active roles based on government policy to stay at home. Parents in Batumirah Village, RT 02/03, realized that during this pandemic period its time parents had to be extra active, especially in various children's activities. Some of the roles played by parents are providing basic introduction to pandemics, increasing the worship, providing motivation, and providing learning assistance at home. This research-based practicum aims to seek the role of parents during the pandemic. The method used is a case study, followed by a moderate participatory approach. While the data used in-depth interviews with research informants. The results showed that the many roles of parents in mentoring were dominated or played by mothers, especially in learning children at home. Even though the role of the family is still running well, there are some parents who cannot play an optimal role or are a little ignore cause of busy. With the reason that parents uneducated so that learning at home cannot be done, as teachers done at school.AbstrakPemberdayaan merupakan sebuah aktivitas di mana seseorang keluar dari situasi yang tidak berdaya, sehingga mempunyai kekuatan untuk bergerak maju. Dengan demikian ia dapat mempengaruhi kehidupan di lingkungan sekitarnya. Di tengah pandemi, peran orang tua menjadi sangat signifikan. Terutama sebagai pendamping bagi anak-anak yang menjalankan belajar di rumah dengan sistem daring. Misalnya, orang tua di Desa Batumirah, RT 02/03 yang merupakan objek penelitian. Dalam kesehariannya, mereka memiliki tanggung jawab tambahan yakni mendampingi anak belajar di rumah. Praktikum berbasis riset ini bertujuan utuk mengetahui peran orang tua terhadap anak selama masa pandemi. Metode yang digunakan adalah studi kasus, yang diikuti dengan pendekatan partisipatif moderat.Sedangkan pengumpulan data menggunakan metode wawancara mendalam dengan informan penelitian. Hasil penelitian menunjukkan banyaknya peran orang tua dalam pendampingan didominasi atau banyak dierankan oleh ibu, khususnya dalam pembelajaran anak di rumah. Walaupun peran keluarga masih berjalan dengan baik, namun ada beberapa orang tua tidak dapat berperan secara optimal atau sedikit acuh dengan alasan sibuk. Dengan alasan keterbatasan pendidikan yang dimiliki orang tua sehingga pembelajaran di rumah tidak bisa dilakukan sebagaimana layaknya guru di sekolah.